Pengaruh Investasi Asing Langsung, Indeks Kualitas Lingkungan, dan Inflasi terhadap Pertumbuhan Ekonomi Negara-Negara G20 Asia Periode 2014-2024 dalam Perspektif Ekonomi Islam - Raudhah Shalsabillah; Mia Selvina; Alief Rakhman Setyanto (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aimed to analyze the effect of Foreign Direct Investment (FDI), Environmental Performance Index (EPI), and inflation on economic growth in Asian G20 countries, namely China, Indonesia, Saudi Arabia, India, and Japan, during the period 2014–2024 from an Islamic economic perspective. The research used a quantitative approach with secondary data obtained from the World Bank and Yale University. The data were analyzed using panel data regression, including Common Effect Model (CEM), Fixed Effect Model (FEM), Random Effect Model (REM), and Generalized Method of Moments (GMM). The results showed that inflation had a significant and positive effect on economic growth, while FDI and EPI had no significant effect. These findings indicated that maintaining price stability played a more dominant role in stimulating economic growth compared to foreign investment and environmental performance during the research period. From the perspective of Islamic economics, the results highlight the importance of price stability as part of the principles of justice (‘adl) and public interest (maslahah) to achieve sustainable and equitable economic growth.